1992
DOI: 10.1021/jm00102a008
|View full text |Cite
|
Sign up to set email alerts
|

2-(N'-aralkylidenehydrazino)adenosines: potent and selective coronary vasodilators.

Abstract: This study aimed at the development of 2-(N'-aralkylidenehydrazino)adenosines as coronary vasodilators. The reaction of aromatic aldehydes or ketones with 2-hydrazinoadenosine in refluxing methanol formed the target compounds 2-27 as crystalline products in good yields. Two kinds of receptors mediate the actions of adenosine on the heart. Retardation of impulse conduction through the atrioventricular node, the negative dromotropic action, is an example of adenosine's action at an A1 receptor (A1AR) and coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…13 These compounds are thought to produce coronary artery dilatation by activating coronary artery A 2A receptors. 7,21 All of these compounds have limited selectivity for A 2A over A 3 receptors on the basis of radioligand binding assays. This selectivity may be underestimated in binding assays, owing to the fact that there are 2 affinity states of G protein-coupled receptors for agonists, and recombinant A 2A receptors are poorly coupled to G proteins and consequently, bind agonists selectively to the low-affinity receptor conformation.…”
Section: Discussionmentioning
confidence: 99%
“…13 These compounds are thought to produce coronary artery dilatation by activating coronary artery A 2A receptors. 7,21 All of these compounds have limited selectivity for A 2A over A 3 receptors on the basis of radioligand binding assays. This selectivity may be underestimated in binding assays, owing to the fact that there are 2 affinity states of G protein-coupled receptors for agonists, and recombinant A 2A receptors are poorly coupled to G proteins and consequently, bind agonists selectively to the low-affinity receptor conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the guinea pig heart have shown that 2-cyclohexylmethylidinehydrazino-adenosine (WRC-0470) is a highly potent coronary vasodilator that is 14,000-fold more potent at producing coronary vasodilation through activation of A 2A -receptors than it is at producing atrioventricular conduction delay through activation of A 1 -ADO receptors [Niiya et al, 1992]. In the present study, the pharmacological properties of WRC-0470 have been further investigated and compared to ADO in an attempt to determine whether WRC-0470 possesses the desired properties for use as a pharmacological agent in myocardial perfusion imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Selective ligands to characterize the adenosine A 2A receptor have been scarce, unlike A 1selective ligands. Only quite recently truly A 2 selective agonists have become available (Francis et al, 1991;Ueeda et al, 1991aUeeda et al, , 1991bNiiya et al, 1992aNiiya et al, , 1992b, whereas A 2 selective antagonists were still lacking. With the disclosure of 8-styrylxanthines as A 2selective antagonists, however, this gap has been largely filled now (Shimada et al, 1992;Jacobson et al, 1993; for some examples of structures see also Fig.…”
Section: Introductionmentioning
confidence: 99%